Islam Nusantara Di Thailand; Studi Etnografi Ritual Ibadah Muslim di Thailand Selatan - Aliyul Himam (Jurnal Kopis: Kajian Penelitian dan Pemikiran Komunikasi Penyiaran Islam, 2020)
Islam Nusantara or Islamic Nusantara is not just an Islamic concept in Indonesia only. Therefore, this paper focuses on how the manifestation of Islam Nusantara concept in Southern Thailand which refers to the manifestation of Islam Nusantara concept that has been applied in Indonesia. This research uses qualitative research with ethnographic approach. South Thai Muslims have a long relationship with Indonesia in genealogical, historical and cultural exchanges. So there is application of the concept of Islam Nusantara in Thailand with its various culture. The cultural form is grouped into language, practice, culture / custom, art, celebration, and worship. Keywords: Islam Nusantara, Indonesia, Southern Thailand, Ritual, Worship, Culture